Literatura Surda: as produções digitais de textos religiosos em Libras - Nóbrega, Carolina Silva Resende da (2017)
The thesis has been conceived with the main thematic the organization of religious texts in Brazilian Sign Language, separated in literary and non-literary, that identify its use in Deaf Literature. This present paper is reasoned on theoreticians of Deaf Literature, Translation, Textual Production and Religion as PETERS (2000), SUTTON-SPENCE (2005), MOURÃO (2011), OUSTINOFF (2011), JAKOBSON (1971), LEITE (2010), ASSIS SILVA (2012), WIGLES and COLOMBO (1979) and others. This research has been based on analysis of questionnaires with twelve deaf Christian people from different places in Brazil. All the subjects reported their observations about the selected videos on social networks and on DVD. It is necessary to raise questions of use of the religious text, like which are the necessary categories for the sacred texts? Why are these strategies applied and in which parts of text? Is there any possibility of the deaf person to understand the religious text in Brazilian Sign Language without resort to Portuguese? These are the issues that lead us to carry out research that covers organized categories. This thesis aims to draw up categories of religious texts in videos. The purpose of the thesis is to analyze and categorize the digital productions of religious texts; analyzing in Libras the use of comparative lexicons between different religious texts; and highlight the religious texts categorized for the types of Literary and Informative texts in Libras.. The videos are analyzed and categorized by Figure, Costumes, Translation, Narrative and Creation, based on the theories and questionnaires of the subjects in the development of the research. Finally, it is hoped that the religious texts in Brazilian Sign Language can be categorized and inserted as a literary contribution in Deaf Literature.